A dormant T‐cell population with autoimmune potential exhibits low self‐reactivity and infiltrates islets in type 1 diabetes. Issue 7 (22nd April 2022) - Kong, Yuelin; Jing, Yi; Allard, Denise; Scavuzzo, Marissa A.; Sprouse, Maran L.; Borowiak, Malgorzata; Bettini, Matthew L.; Bettini, Maria
Abstract: The contribution of low‐affinity T cells to autoimmunity in the context of polyclonal T‐cell responses is understudied due to the limitations in their capture by tetrameric reagents and low level of activation in response to antigenic stimulation. As a result, low‐affinity T cells are often disregarded as nonantigen‐specific cells irrelevant to the immune response. Our study aimed to assess how the level of self‐antigen reactivity shapes T‐cell lineage and effector responses in the context of spontaneous tissue‐specific autoimmunity observed in NOD mice. Using multicolor flow cytometry in combination with Nur77 GFP reporter of TCR signaling, we identified a dormant population of T cells that infiltrated the pancreatic islets of prediabetic NOD mice, which exhibited reduced levels of self‐tissue reactivity based on expression of CD5 and Nur77 GFP . We showed that these CD5 low T cells had a unique TCR repertoire and exhibited low activation and minimal effector function; however, induced rapid diabetes upon transfer. The CD4 + CD5 low T‐cell population displayed transcriptional signature of central memory T cells, consistent with the ability to acquire effector function post‐transfer. Transcriptional profile of CD5 low T cells was similar to T cells expressing a low‐affinity TCR, indicating TCR affinity to be an important factor in shaping CD5 low T‐cell phenotype and function at the tissue site. Overall, our study suggests that autoimmune tissue can maintain a reservoir of undifferentiated central memory‐like autoreactive T cells with pathogenic effector potential that might be an important source for effector T cells during long‐term chronic autoimmunity. Abstract : Low level of CD5 expression identified phenotypically dormant T cells with autoimmune potential, which was revealed upon cell transfer. Transcriptional signature indicated stem‐cell memory‐like phenotype and was similar to low‐affinity insulin‐specific T cells, suggesting that TCR affinity guides autoimmune T‐cell fate decisions and stem‐like capacity.